Notes in connexion with twelve Autograph Letters by Major-General James Wolfe, who fell at the Capture of Quebec on 13th September 1759, addressed to Captain, afterwards Lieut.-Colonel William Rickson, Quarter-master General of North Britain (Proceedings of the Society of Antiquaries of Scotland, 1863)
On the day, John Buchanan exhibited and donated some letters written by General James Wolfe to the Society’s collections. He highlights their provenance and importance to the study of Wolfe’s life and character. There is also some discussion of the person who the letters were addressed to, William Rickson.